PRODUKTIVITAS KATA HARASSMENT BERKOMPOSISI DALAM BAHASA JEPANG - Luhur Wedayanti, Ni Putu (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2015)
ABSTRACT Japan has a lot of loanwords, not only from China but also from English or other countries to enrich their language. The word harassment compounded with other words or phrases form new meaning refers to the feeling of uncomfortable or unconvenient of something. The word harassment coumpounded in Japanese seems to have trivilisation in meaning, this phenomenon related to high sensitivity and strict value in Japanese society.Keyword: loanword, Japanese, harassment